François Valentijn; Antara etika dan estetika - Leirissa, R. Z. (UI Scholars Hub, 2008)
A controversial book on the history of the VOC in the seventeenth century was written by Fran ois Valentijn, a preacher in the payroll of the Dutch East India Company (VOC). The book (eight volumes), published in 1724-1726, was known by its popular title Oud en Nieuw Oost-Indi n. Most of the materials in the book were pirated from other sources without acknowledging their authors as is the proper practice of historiography. But as to its style, a number of Dutch writers appreciated its esthetic qualities. Beside that, the book is indeed useful to historians today because some of the materials pirated in the book have now been lost forever.